Tantangan dan Arah Dakwah di tengah Ancaman Pendemi Covid-19 - Juhari (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Da'wah is a duty of Islamic syar'i that given to every Muslim according to their abilities. In the running of da'wah, it is always faced with various challenges in every space and time. Currently, da’wah is being faced with a global and an invisible challenges, covid-19. This virus had choked up the dakwah movement, the interaction between the da'i and mad'u was hindered by the procedure of social distancing. Therefore, the direction of da’wah in the era of Covid-19 needs to be formulated. To find the ideal direction of da'wah, the research has been done at the “Forum Dakwah Perbatasan (FDP)”that located in the capital city of Aceh Province. This forum is ane of the Islamic organizations that are committed to carrying out da'wah even in the midst of a covid storm. The data that related to the challenges and direction of da'wah were obtained through in-depth interviews, documentation in the office of FDP and observations in the FDP da'wah area, especially in Danau Paris District, Aceh Singkil and in Lhokseumawe City. Based on the understanding and analysis of the data, the direction of da’wah carried out by this organization emphasizes the development of education, economic strengthening and humanitarian assistance, and health campaigns. So, the activities of da'wah is still running well while maintaining of health protocols.